The Ideal Body: A Social Construct? Reflections on Body Pressure and Body Ideal Among Students in Upper Secondary School - Sæle, Ove Olsen; Sæther, Ida Kathrine; Viig, Nina Grieg (Frontiers in Sports and Active Living, 2021)
Several studies show that young people today are negatively impacted by body image ideals in social media. We studies young people's reflections on body image and body pressure. More precisely: How does a selected group of third-year upper secondary school students understand their body images and body pressures through social media? Eight third-year students, four of each gender, were interviewed from two upper secondary schools in a medium-sized city in Norway. An interesting find was that body pressure was not experienced solely as one-sided pressure exerted externally by media sources, but that they also personally influenced others through their own active use of social media channels like Facebook and Instagram. They reported having experienced body pressure in their own lives and in their immediate environment, and that both genders are affected. The study builds on sociocultural body theory based on Foucault's ideas and work, but also uses more recent media theory for the analysis and discussion. A BOPS model developed by the researchers was used for the operational parameters that is centered around the concepts of panopticon, synopticon and omniopticon.